(untitled) (The Strategic Review for Southern Africa, 2021)
The promotion of peace and security in Africa necessitates security cooperation between states and collective security remains a way to pursue it. This paper explores the changed meaning and application of the concept of collective security within the African Peace and Security Architecture (APSA) to deal with both interstate and intrastate security concerns within the African Union (AU). Since the AU has made clear commitments to collective security, the aim is to determine to what extent the AU subscribed to collective security and applied it in terms of coercion, which includes interventions. While dealing with genocide, war crimes and extended presidential terms remains problematic, the AU has taken an assertive stand with the use of coercion in cases of unconstitutional changes of government. The article highlights the tension between the theory and practice of collective security in Africa.